Diagnosis and Successful Surgical Management of Concomitant Granulosa Cell Tumor and Pyometra in a Beagle Dog: A Case Report - Kumar, Sushil; Singh, Kiran; Biswas, Newton (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Ovarian tumor arises from the uncontrolled and abnormal  proliferation of cells located in the ovary. It mostly affects  older female dogs, especially the unspayed ones. The overall  prevalence of ovarian tumours is 0.5% to 1.2%, but is as high  as 6.25% in intact female dogs (Bhoi et al., 2022). Based on  their origin, canine ovarian tumors are categorized into three  groups: germ cell tumors, sex cord-stromal tumors, and  epithelial cell tumors (Kennedy 1998). Granulosa cell tumors  (GCTs) that originate from sex cord stromal cells are one of  the most commonly reported neoplasms in canine ovary. This  accounts for about 50% of all ovarian tumors (Diez-bru et al.,  1998). GCTs cause increase in ovarian hormone levels such  as estradiol, progesterone and inhibin-A (Pluhar et al., 1995).  This increased hormonal secretion leads to development  of clinical symptoms like persistent estrus, vulvar swelling  with discharge, slow movement and especially persistent  abdominal enlargement. It can also cause nymphomania,  virilization, hyperadrenocorticism, alopecia and sometimes  complicated mammary carcinoma (Headley et al., 2006;  Buijtels et al., 2010; Chung et al., 2013). GCTs in bitches  have various microscopic appearances, such as follicular,  cystic or poly cystic, and solid. The more important and  prominent pattern in some GCT is follicular solid sheet,  cords, trabecular, or nests (Buijtels et al., 2010). Histologically,  granulosa cells in this tumor are similar to normal granulosa  cells and are often arranged like normal Graafian follicles.  ET-1 (endothelin) and ET-A (endothelin-A receptor) are over expressed in canine ovarian tumours, suggesting a potential  role of these two molecules in canine ovarian carcinogenesis  (Borzacchiello et al., 2010). Diagnostic tools like radiography  and ultrasonography play vital role in early identification of  tumors like GCTs. The present case report records diagnosis  and surgical management of ovarian tumour (Granulosa Cell  Tumour) and pyometra in a ten year old Beagle dog.
Keywords: immunoprophylaxis; vulvar swelling